Sensitivity of ventricular systolic function to afterload during veno‐arterial extracorporeal membrane oxygenation. (1st July 2022) - Ng, Pauline Yeung; Ma, Tammy Sin Kwan; Ip, April; Lee, Man Kei; Ng, Andrew Kei‐Yan; Ngai, Chun Wai; Chan, Wai Ming; Siu, Chung Wah; Sin, Wai Ching
Abstract: Aims: Veno‐arterial extracorporeal membrane oxygenation (V‐A ECMO) increases afterload to the injured heart and may hinder myocardial recovery. We aimed to compare the sensitivity of left ventricular (LV) systolic function to the afterload effects of peripheral V‐A ECMO during the acute and delayed stages of acute myocardial dysfunction. Methods and results: A total of 46 adult patients who were supported by peripheral V‐A ECMO between April 2019 and June 2021 were analysed. Serial cardiac performance parameters were measured by transthoracic echocardiography (TTE) on mean day 1 ± 1 of V‐A ECMO initiation ( n  = 45, 'acute phase') and mean day 4 ± 2 of V‐A ECMO initiation ( n  = 36, 'delayed phase'). Measurements were obtained at 100%, 120%, and 50% of ECMO target blood flow (TBF). LV global longitudinal strain (GLS) significantly improved from −6.1 (−8.9 to −4.0)% during 120% TBF to −8.8 (−11.5 to −6.0)% during 50% TBF ( P  < 0.001). The sensitivity of LV GLS to changes in ECMO flow was significantly greater in the acute phase of myocardial injury compared with the delayed phase [median (IQR) percentage change: 72.7 (26.8–100.0)% vs. 22.5 (14.9–43.8)%, P  < 0.001]. Findings from other echocardiographic parameters including LV ejection fraction [43.0 (29.1–56.8)% vs. 22.8 (9.2–42.2)%, P  = 0.012] and LV outflow tract velocity‐time integral [45.8 (18.6–58.7)% vs. 24.2 (12.6–34.0)%, P  = 0.001] were similar. A total of 24 (52.2%) patients were weaned off ECMO successfully. Conclusions: We demonstrated that LV systolic function was significantly more sensitive to the afterload effects of V‐A ECMO during the acute stage of myocardial dysfunction compared with the delayed phase. Understanding the evolution of the heart–ECMO interaction over the course of acute myocardial dysfunction informs the clinical utility of echocardiographic assessment in patients on V‐A ECMO.